A novel amidotransferase required for lipoic acid cofactor assembly in Bacillus subtilis - Christensen, Quin H. (2011)
In the companion paper we reported that Bacillussubtilis requires three proteins for lipoic acid metabolism,all of which are members of the lipoate proteinligase family. Two of the proteins, LipM and LplJ, havebeen shown to be an octanoyltransferase and alipoate : protein ligase respectively. The third protein,LipL, is essential for lipoic acid synthesis, but hadno detectable octanoyltransferase or ligase activityeither in vitro or in vivo. We report that LipM specificallymodifies the glycine cleavage system protein,GcvH, and therefore another mechanism mustexist for modification of other lipoic acid requiringenzymes (e.g. pyruvate dehydrogenase). We showthat this function is provided by LipL, which catalysesthe amidotransfer (transamidation) of the octanoylmoiety from octanoyl-GcvH to the E2 subunit of pyruvatedehydrogenase. LipL activity was demonstratedin vitro with purified components and proceeds via athioester-linked acyl-enzyme intermediate. As predicted,DgcvH strains are lipoate auxotrophs. LipLrepresents a new enzyme activity. It is a GcvH:[lipoyldomain] amidotransferase that probably uses a Cys-Lys catalytic dyad. Although the active site cysteineresidues of LipL and LipB are located in differentpositions within the polypeptide chains, alignment oftheir structures show these residues occupy similarpositions. Thus, these two homologous enzymeshave convergent architectures.